(untitled) (Research, Society and Development, 2022)
The demand for forest restoration projects grows increasingly in the State of Amapá. One of the difficulties that these projects are having is the lack of knowledge about the regional offer of seedlings of native species. This study aims to evaluate the nurseries and seedling production of species from the Ferreira Gomes and Porto Grande Amzonian Forest in the state of Amapá. The field work consisted of visits to the 7 nurseries surveyed, in which was applied an structured questionnaire addressing various topics related to the nursery and the seedling production, requested a list of the species produced and performed the photographic record of the nursery. In the diagnostic were included the nurseries producing seedlings of Amazonian Forest species, regardless of the amount, purpose and destination of then. Regarding the administrative structure, the nurseries of the Ferreira Gomes and Porto Grande, are mostly small sized, administered by private agencies and many of them lacks infrastructure for seedling production. Only one of seven nurseries are registered to the RENASEM / MAPA as required by the current legislation. The seedlings are produced with low diversity of species, predominance of plastic bags as recipients and little technical and managerial control over the production. The data shows that the activity still have a lot to develop in the Ferreira Gomes and Porto Grande, being necessary public policies aiming reinforce the existing nurseries, stimulate Amazonian Forest restoration plantations and, consequently, the demand for native forest seedlings.